Tectonics Problems of Regional Settings - Sharkov, Evgenii V. (IntechOpen, 2018)
This book is devoted to different aspects of tectonic researches. New results and interpretations are presented here for diverse tectonic settings. Most of the chapters include up-to-date materials of detailed geological investigations, often combined with geophysical data, which can help understand more clearly the essence of mechanisms of different tectonic processes. Some chapters are devoted to the tectonic evolution of regions (East Antarctica, East Kazakhstan, Mongolo-Okhotsk orogenic belt), and others have dealt with the different aspects of tectonic events: influence of detachment structural deformation on pore structure evolution in shales, evolution of drainage in response to brittle-ductile dynamics and surface processes, soft sediment deformation structures triggered by the modern earthquakes, and post-opening deformation history of the Japan Sea back-arc basin.